Students’ Learning Motivation and Their English Learning Achievement: A Correlational Study at SMAN 1 Ranah Pesisir - Nasrahtul Husnah; Edi Trisno (Universitas Negeri Padang, 2023)
In the learning process, learning motivation is one of the factors that influence students’ learning achievement. This research is about students’ learning motivation and their English learning achievement: A correlational study at SMAN 1 Ranah Pesisir. This research was quantitative and used a correlational technique with 329 Phase E students as population. The sample for this research was 66 students chosen by proportional random sampling techniques. The data were collected through questionnaire and English examination test result in even semester. Prior to finding out correlational, the research tried to ascertain students’ learning motivation level and students’ English learning achievement level. The research found out that students’ learning motivation level in moderate category. On students’ English learning achievement, the Phase E students got poor level. For correlation, the study used Pearson Product Moment. The research revealed that there is a correlation between students’ learning motivation and their English learning achievement in the weak category. It was shown by the rvalue= 0,397. It means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.